PENDAMPINGAN BELAJAR SISWA LAMBAT BELAJAR (SLOW LEARNER) (STUDI KASUS PADA SISWA MI ISLAMIYAH MUHAMMADIYAH WALIKUKUN) - DARMANTO, DARMANTO (LPPM STIT Muhammadiyah Tempurejo Ngawi, 2022)
Slow learner is a condition where children have cognitive delays in receiving, understanding, and mastering the information they receive. This study aims to conduct a study on the pattern of student mentoring slow learners. The research uses a qualitative approach with a case study method. Data collection techniques used are observation, interviews, and documentation. The results showed that one of the factors that influenced children to experience slow learners was the family environment, and the pattern of mentoring carried out was with a personal approach, namely approaching and understanding children in depth with the aim of knowing the child's tendencies in learning, in addition to establishing communication in a holistic manner. intensively with parents, in order to provide motivation to learn for the child